Penerapan Mesin Perontok Padi Untuk Peningkatan Kualitas Produksi Pada Gabungan Kelompok Tani “Tani Mukti” - Santoso , Eko Budi; Purkuncoro, Aladin Eko; Hutabarat, Julianus (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Malang City, apart from being a city of education, has also developed small industries to support the development of the city. Rice is one of Indonesia's products, especially for the Indonesian people themselves. Because the staple food of Indonesian people is rice. So many rice farmers in Sukun Subdistrict, Malang City, especially in the Bandungrejosari area. The main obstacle faced by farmers is that in addition to limited capital, they also do not have adequate production support equipment. The process of threshing rice seeds is done traditionally using human labor so that the production process takes a very long time. This constraint causes low productivity of rice grains. With this argument, it is necessary to make a rice thresher machine that can improve the quality of production. This activity aims to apply Engineering Technology, this is the development of appropriate technology equipment to utilize the power of the rice thresher machine, the threshing process is faster and maximum to increase the efficiency of production time. With the application of the use of the developed rice thresher machine, it is hoped that it can help the MSME industry in running its business properly and profitably. The impact obtained from this activity is that this tool from an economic point of view is expected to have an impact on increasing income as a consequence of increasing production capacity. With the increase in production capacity, the demand for this commodity from rice farmers will also increase so that it can indirectly increase the income of the farmers themselves.